Clinical reasoning in dental students: a comparative cross-curricula study - Nafea, Ebtihaj (2015)
Clinical reasoning is a skill required by all health professionals in managing patients. Research in clinical reasoning has come mostly from medicine and nursing, less from dentistry. The effect of curriculum on the development of clinical reasoning is still not well understood. Moreover, no research has been conducted to understand what clinical reasoning means to students and what educational strategies are valued by them. The aim of this research is to explore the effect of different educational strategies in different dental schools on clinical reasoning and to discover how students perceive clinical reasoning.